Toward a Uniform Consumer Credit Code: Discussion - Barrett, Roger S.; Fand, David I.; Mayer, Robert C. (Journal of Finance, 1968)
Roger S. Barrett, David I. Fand, Robert C. Mayer, Toward a Uniform Consumer Credit Code: Discussion, The Journal of Finance, Vol. 23, No. 2, Papers and Proceedings of the Twenty-Sixth Annual Meeting of the American Finance Association Washington, D.C. December 28-30, 1967 (May, 1968), pp. 320-330